2015
DOI: 10.1021/acs.jpca.5b10312
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Limited Signatures of Quantum Coherence

Abstract: The observation of persistent oscillatory signals in multidimensional spectra of proteinpigment complexes has spurred a debate on the role of coherence-assisted electronic energy transfer as a key operating principle in photosynthesis. Vibronic coupling has recently been proposed as an explanation for the long lifetime of the observed spectral beatings. However, photosynthetic systems are inherently complicated, and tractable studies on simple molecular compounds are in demand to fully understand the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
(156 reference statements)
1
17
0
Order By: Relevance
“…The studied D2F complex exhibits a long-term coherence that is comparable to the ones experimentally found in some light-harvesting and organic materials 3,4,[16][17][18] . As shown in Fig.…”
Section: A Solvent and Temperature Effectssupporting
confidence: 77%
See 1 more Smart Citation
“…The studied D2F complex exhibits a long-term coherence that is comparable to the ones experimentally found in some light-harvesting and organic materials 3,4,[16][17][18] . As shown in Fig.…”
Section: A Solvent and Temperature Effectssupporting
confidence: 77%
“…From a perspective of novel materials and technologies for solar energy conversion, organic photovoltaic (OPV) sytems have attracted significant attention [7][8][9] due to the enhancement of their power conversion efficiency (PCE) 5,6 , flexibility,manufacturing reduction costs, and high-temperature production of cells [10][11][12][13][14] . On a different facet, but complementary to this development, quantum coherence has, over the past decade, been experimentally linked to early-stage energy transfer in light harvesting photosynthetic complexes [1][2][3][4][15][16][17][18][19] ; in particular, time-resolved ultrafast optical and electronic spectroscopies have evidenced oscillations of exciton state populations lasting up to a few hundred femtoseconds, which have been attributed to quantum coherence emerging as a result of initially prepared laser pulses [1][2][3][4][15][16][17][18] . This two-way breakthrough poses an intriguing question about the possible functional role of quantum coherent effects as a precursor of efficient ET in materials and biological systems under structural and energetic disorder at physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to our calculated results, this peak is somewhat red-shifted in the measurements, which is a known distortion owing to the finite pulse bandwidth. 46 Regardless, both the experimental and numerical spectra show no discernible features around ω 1 = 1.72 eV, which corresponds to the energy of TT 1 , implying that the S 0 −TT 1 transition between these states is indiscernible through static 2D spectra. However, as was first demonstrated in Ref.…”
Section: A Static 2d Spectramentioning
confidence: 89%
“…We have demonstrated that a redshifted laser spectrum can be used to selectively prepare coherences in the ground state, thus complementing experiments where the spectrum causes the ambiguity we reported. The effect of the laser spectrum on coherences has been recently discussed in the literature, but the filtering effect was not discussed [48]. The selection of specific pathways through two-color experiments has also been described [49][50][51], but the concept that some vibronic signatures may be missing in one-color experiments, as described here, was previously only briefly noted by Butkus et al [52].…”
mentioning
confidence: 84%